Clima laboral y motivación del personal técnico mecánico de Mannucci Diesel Cajamarca SAC, 2021 - Morillo Jiménez, Irma Shary (2022)
The present investigation was carried out with the purpose of analyzing the influence of the work environment on the motivation of the Mechanical Technical staff of Mannucci Diesel Cajamarca SAC. The sample is made up of 40 workers from the Contracts and Heavy Services area. In the development of this research, methods such as inductive-deductive, analytical-synthetic and the statistical method will be applied. Scientific research techniques such as interviews, survey observation and bibliographic review were also used, which were presented through the interview guide instruments, interview record, observation guide, observation record, questionnaire and documentary sources, which gave results. in quantitative and qualitative data that allow the analytical understanding of the indicators and their variables. According to the analysis carried out and the results obtained in the investigation, it is evident that the work environment positively influences the motivation of the Mechanical Technical staff of Mannucci Diesel Cajamarca SAC, evidenced in the high sense of belonging, knowledge of the organizational culture, participation in productive activities, adequate teamwork and adequate interpersonal relationships.